CFD Study On The Performance Of Oxygen Lance For Partial Combustion Unit At Direct Reduction Plant - Jolius, Gimbun; Mohd Irwan Shah, Md Zain (2011)

(untitled)
This paper presents Computational fluid dynamics (CFD) study of temperature profile generated by the partial oxidation process at the direct reduction plant. The simulation was performed using standard k-ε (SKE) viscous model and Eddy Dissipation (ED) turbulence-chemistry interaction model. Two different designs of different oxygen lances being used in predicting the temperature profile generated; the normal configuration according to local industry and lances attached with wings at the bottom part. The predicted turbulence velocity and the temperature reading inside the system were found to be increased when using the second lances configuration as compared to the current configuration used in the plant. Predictions from CFD model were found to be in good agreement about 10% difference to the experimental data obtained from experimental work. This modelling exercise has demonstrated a cost effective route of design optimisation for Partial Combustion Unit (PCU) and hence should be used as tool for troubleshooting a design in future.